Glocalization Self-Referential Remembrances (Glocalism: Journal of Culture, Politics and Innovation, 2020)
This intervention is comprised of a sketch of the ways in which I have encountered the concept of glocalization, as well as glocality, during the past thirty-forty years. In one sense this means that it is extra-autobiographical. In saying this I have strongly in mind the not infrequent maxim that all good sociology, as well as anthropology and other social sciences, are at the same time extra-autobiographical. As will be seen in what follows this relationship between the autobiographical and the extra-autobiographical is part and parcel of the intellectual image that is presented here. My first conscious encounter with the word and idea of glocalization was an indirect result of the intellectual concern that I developed with globalization in the 1980s or, perhaps, even before then. It should be said in this respect that there were a number of binaries that were prominent in social scientific discourse in the 1960s and 1970s that undoubtedly had a strong bearing on my thinking about globalization and later glocalization. These included such conceptions as cosmopolitanism-localism and various others of that nature. Even less obvious were such distinctions as transcendence-immanence and sacred-profane. The genealogy inspired by such binaries were undoubtedly in my mind as I began explicitly to enter what might well be called the “glocal fray”. Moreover, I was to learn after I first used the concept of glocalization in 1992 that an anthropologist, Eric Swyngedouw, had used this concept around the same time as myself; both of us inspired by Japanese business discourse. As the 1990s wore on more and more people joined in the debate with varying degrees of hostility and enthusiasm, more frequently the former than the latter. In tracing this history, I shall obviously speak about the changes in, and fortunes of, the better-known concept of globalization as well as the “lesser” concept of localization. Being a sociologist – more appropriately now, a transdisciplinarian – I shall also focus upon the increasingly significant branch of social/natural science that addresses such issues as climate change, biodiversity and the debate about the Anthropocene. This paper is being composed during the tragic and global phenomenon of the Covid-19 pandemic. The latter surely exhibits glocal characteristics in the large.
Keywords: glocalization; glocality; globalization; glocal fray; social sciences